Differential and Difference Equations with Applications Contributions from the International Conference on Differential & Difference Equations and Applications - Pinelas, Sandra; Chipot, Michel; Dosla, Zuzana; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The volume contains carefully selected papers presented at the International Conference on Differential & Difference Equations and Applications held in Ponta Delgada – Azores, from July 4-8, 2011 in honor of Professor Ravi P. Agarwal. The objective of the gathering was to bring together researchers in the fields of differential & difference equations and to promote the exchange of ideas and research. The papers cover all areas of differential and difference equations with a special emphasis on applications.
Ondrej Dosly -- Robert Finn -- Nadezhda Konyukhova -- Roman Koplotadze -- Sergey Korotov -- Ulrich Krause.-Jean Mawhin -- Felix Sadyrbaev -- Stefan Siegmund -- I.P. Stavroulakis -- Jeff Webb -- Patricia Wong -- Agacik Zafer -- Fábio Zanolin -- María Anguiano -- Irina Astashova -- Basem Attili -- Giles Auchmuty -- Blanka Baculikova -- Jung-Chao Ban -- Luciano Barbanti -- Michal Benes -- Joel Blot -- Gabrielle Bonanno -- Alberto Boscaggin -- Pasquale Candito -- Tomás Caraballo -- Valery Covachev -- Miguel Brito da Cruz -- Irada Dzhalladova -- Jozef Dzurina -- Svetlana Ezhak -- Silvia Gago -- Isaac A. García -- Shapour Heidarkhani -- Gabriela Holubova -- Gennaro Infante -- Vladimir Jacimovic -- Fatma Karakoc -- Elena Karulina -- Elena Kostousova -- Pedro Lima -- Somayeh Mahdavi -- Natália Martins -- Helena Melo -- Maryam Mirzapour -- Mesliza Mohamed -- Maria Luisa Morgado -- Ralph Oberste-Vorth -- Ana Pedro -- Stella Vernier Piro -- Andrejs Reinfelds -- Helia Serrano -- Naoki Shioji -- Walter Sizer -- Francisco Suárez-Grau -- Volodymyr Sushch -- Vladimir Vasilyev -- Junfang Zhao -- Nikolaos Zographopoulos.
Keywords: Differential equations; Partial differential equations; Difference equations; Functional equations; Dynamics; Ergodic theory; Integral equations; Ordinary Differential Equations; Partial Differential Equations; Difference and Functional Equations; Dynamical Systems and Ergodic Theory; Integral Equations